Screening and Evaluation of Mean Infestation Rate of Aeolesthes holosericea Fabricius in Different Age Groups of Apple Cultivars during 2008-2011 in Jammu Province (J&K), India - Gupta, Ruchie (Indian Forester, 2016)
No Abstract.